Reading Strategies In English As Foreign Language Students At English Education & Literature Program - Dina Fitriana (Universitas Pahlawan Tuanku Tambusai, 2022)
The aim of the research is to know the reading strategies frequently used by EFL students at English Education and Literature program while they read English academic text in reading subject. Top-down strategies were used by EFL students at English Education and Literature program. Bottom-up strategies were used by EFL students at English Education and Literature program. Students’ reading strategies tendencies in top-down and bottom-up strategy at English Education and Literature programme. The participants of this research were 70 students. This research was designed in qualitative frameworks. Data were taken through a survey and classroom observations. The survey data were taken through questionnaire. The data from observation and questionnaire were analyzed by counting the score of all participants based on Likert-scale. The research findings are: 1) English Education Students frequently used bottom-up strategy with the percentage 34.3% higher than Literature students with 4.06%. And the students in Literature program frequently used top-down strategy with the percentage 35.7% higher than Education Program with 9.9%. 2) The top-down strategies were always and usually used by the literature students with 34.4%; trying to find the topic sentence, introduction and conclusion of the text, and 51.4% students usually skim for gist of the text or to identify the main ideas, themes, or concepts and pay attention to how ideas and facts are used to support the main ideas.. 3) The bottom-up strategies were always used by the English Education Program students with 45.7%; usually notice the cohesive ties like